Mixed bayesian implementation in general environments - KUNIMOTO, Takashi (Institutional Knowledge at Singapore Management University, 2019)
A social choice rule is said to be mixed Bayesian implementable if one can design a mechanism (or institution) in which the set of all mixed Bayesian Nash equilibrium outcomes coincides with that specified by the rule. The objective of this paper is to generalize the results of mixed Bayesian implementation. By means of example, I first assess the implication of common priors in Bayesian implementation. Second, I identify a mild condition that fills the gap between the necessity and sufficiency for mixed Bayesian implementation in general environments including non-economic ones. Third, I establish some new results to unify the literature of Bayesian implementation and Nash implementation.